2003
DOI: 10.1051/0004-6361:20030367
|View full text |Cite
|
Sign up to set email alerts
|

Atomic data for the K-vacancy states of Fe XXIV

Abstract: Abstract. As part of a project to compute atomic data for the spectral modeling of iron K lines, we report calculations and comparisons of atomic data for K-vacancy states in Fe . The data sets include: (i) energy levels, line wavelengths, radiative and Auger rates; (ii) inner-shell electron impact excitation rates and (iii) fine structure inner-shell photoabsorption cross sections. The calculations of energy levels and radiative and Auger rates have involved a detailed study of orbital representations, co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 60 publications
1
73
0
Order By: Relevance
“…The branching ratios for many ions of astrophysical interest have been given by Kaastra & Mewe (1993) and updated calculations for some systems have been given by Bautista et al (2003), Gorczyca et al (2003Gorczyca et al ( , 2006, Palmeri et al (2003), Mendoza et al (2004), and Shevelko et al (2005). For completeness, we mention that another scaling for EIMI cross sections has been given by Fisher et al (1995).…”
Section: Fitting Formulaementioning
confidence: 99%
“…The branching ratios for many ions of astrophysical interest have been given by Kaastra & Mewe (1993) and updated calculations for some systems have been given by Bautista et al (2003), Gorczyca et al (2003Gorczyca et al ( , 2006, Palmeri et al (2003), Mendoza et al (2004), and Shevelko et al (2005). For completeness, we mention that another scaling for EIMI cross sections has been given by Fisher et al (1995).…”
Section: Fitting Formulaementioning
confidence: 99%
“…The effects of configuration interaction from high-energy configurations have been investigated in iron K-shell data by Bautista et al (2003) and Palmeri et al (2003), who found that the configurations with n = 3 have little effect on the accuracy of the 1s−2p transition atomic data from Fe xviii to Fe xxv, either for energy levels or for radiative rates. For example, differences lower than 2% are found for radiative rates when the n = 3 configurations are included in Fe xxiv .…”
Section: Calculationsmentioning
confidence: 99%
“…Auger rates are computed in both HFR and AUTOSTRUCTURE in a distorted wave approach. The Auger decay channels considered in the present calculations and the configuration-interaction (CI) expansions used are the same as in our previous papers on the Fe isonuclear sequence (Bautista et al 2003;Palmeri et al 2003a,b;Mendoza et al 2004). Concerning the open-3d-shell ions, we employ the formula given in Palmeri et al (2001) for single-configuration averaged Auger decay rates…”
Section: Calculationsmentioning
confidence: 99%
“…Following extensive work by Palmeri et al (2002Palmeri et al ( , 2003a, Bautista et al (2003Bautista et al ( , 2004, Mendoza et al (2004) and Kallman et al (2004) on Fe K lines; García et al (2005) on the K-shell photoabsorption of O ions; Palmeri et al (2008a) on the Ne, Mg, Si, S, Ar and Ca K lines; Palmeri et al (2008b) on the Ni K lines; García et al (2009) on the K-shell photoionization and photoabsorption of N ions; by Witthoeft et al (2009) …”
Section: Introductionmentioning
confidence: 99%